2012
DOI: 10.1108/15253831211286255
|View full text |Cite
|
Sign up to set email alerts
|

Regional strategies, liability of foreignness, and firm performance

Abstract: PurposeThis paper seeks to analyze the performance implications of the regional and global strategies pursued by multinational companies. It aims to argue that a firm could experience different performance effects for its intra‐ and inter‐regional operations due to differences in the liability of foreignness between these two levels.Design/methodology/approachUsing a large sample of multinational enterprises (MNEs) drawn from all triad regions during the period 1998‐2008, the paper uses panel data methods to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…Amongst the FMNEs, 37 percent (61) were headquartered in countries in the same region as the SMOPEC where they operated (region was defined by continent (i.e. Europe, Asia and Australia) see Kudina (2012)), with the remainder (63 percent or 104) originating from outside the region. Almost all FMNEs originated from developed economies, with 37 percent headquartered in the US.…”
Section: Survey Design and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst the FMNEs, 37 percent (61) were headquartered in countries in the same region as the SMOPEC where they operated (region was defined by continent (i.e. Europe, Asia and Australia) see Kudina (2012)), with the remainder (63 percent or 104) originating from outside the region. Almost all FMNEs originated from developed economies, with 37 percent headquartered in the US.…”
Section: Survey Design and Data Collectionmentioning
confidence: 99%
“…In H2, FMNE was divided into dummy variables, where 1 indicated that the FMNE originated from the same region (H2.0), and 0 if the FMNE originated from outside region (H2.1). Specifically, home countries within the same continent as the SMOPEC were considered to be within the region, and others were outside the region (Kudina, 2012). Where countries did not belong to a continent, i.e.…”
Section: Table II About Herementioning
confidence: 99%
“…This stream of research follows the argument made by Hymer (1960) that foreign firms lack information, network and face discrimination in the host country. Thus, to overcome the costs, foreign firms need to choose a suitable entry mode to learn and acquire resources, knowledge and information in the environment (Acheampong and Dana, 2017; Asmussen and Goerzen, 2013; Elango, 2009; Kudina, 2012). Another stream of research argues that LOFs affect MNE expansion strategy where firms tend to face lower LOFs within the same regional area (Asmussen, 2009) or global cities (Goerzen et al , 2013; Nachum, 2003).…”
Section: Liabilities Of Foreignness and Assets Of Foreignness: Concep...mentioning
confidence: 99%
“…(3) costs resulting from the host country environment, such as the lack of legitimacy of foreign firms and economic nationalism; (4) costs from the home country environment, such as restrictions on high-technology sales to certain countries. Four sources of LOF are traditionally assumed to be the point of departure in the absolute majority of both key empirical and conceptual papers devoted to analyzing LOF phenomenon (Nachum, 2003;Eden & Miller, 2004;Denk et al, 2012;Kudina, 2012;Moeller et al, 2013;Zhou & Gullien, 2016). Among widely used theories to analyze LOF phenomenon are theories of international expansion (Bai et al, 2013;Wei & Clegg, 2015); social network theory (Chen et al, 2016;Tiwari et al, 2016); institutional theory (Bell et al, 2012;Edman, 2016); resource based view (Miller et al, 2008;Cuervo-Cazurra & Un, 2015) including those emphasizing firm-specific advantages (Zaheer & Nachum, 2011;Kolk et al, 2014); population ecology (Li et al, 2008) and others.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…The phenomenon of additional costs which firms face when doing business abroad is one of intensively discussed topics in academic literature (Zaheer, 2002;Nachum, 2010;Kudina, 2012). Since the first widely recognized formulation of this problem in Hymer's dissertation in 1960 and later on in his book (Hymer, 1960(Hymer, , 1976, this phenomenon has received considerable attention from academic community and resulted in a massive array of concepts aimed at its operationalization: "costs of doing business abroad" (Hymer, 1960(Hymer, , 1976; "liability of foreignness" (LOF) (Zaheer, 1995); "liability of emergingness" (Madhok & Keyhani, 2012); and even some imitative concepts departing from the original field and content of the term, such as "liability of origin" (Kolk & Curran, 2016); "liability of privateness" (Bhanji & Oxley, 2013), to name a few.…”
Section: Introductionmentioning
confidence: 99%